2013
DOI: 10.1007/s00247-013-2844-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic protocol for assessment of the validity of BOLD MRI in a rabbit model of inflammatory arthritis at 1.5 tesla

Abstract: The most clinically relevant reading parameters included a lower threshold of r > 0.01 and a positive + negative BOLD response. We propose that diff_on_off is a more clinically relevant summary measure of BOLD MRI, while PT% can be used as an ancillary measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These methods have inherent shortcomings, which are mainly uncertainty and cost. For animal experiments, most investigators have resorted to euthanizing animals to obtain results on local disease status 27,28. Ultrasound‐guided biopsy in patients has been accepted as a minimally invasive and safe approach, which is well tolerated by patients while enabling the collection of high‐quality synovial tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have inherent shortcomings, which are mainly uncertainty and cost. For animal experiments, most investigators have resorted to euthanizing animals to obtain results on local disease status 27,28. Ultrasound‐guided biopsy in patients has been accepted as a minimally invasive and safe approach, which is well tolerated by patients while enabling the collection of high‐quality synovial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For animal experiments, most investigators have resorted to euthanizing animals to obtain results on local disease status. 27,28 Ultrasound-guided biopsy in patients has been accepted as a minimally invasive and safe approach, which is well tolerated by patients while enabling the collection of high-quality synovial tissues. This study has shown that this insight can also be extrapolated to experimental RA in rabbits, which should allow more preclinical longitudinal studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Development and application of new technologies that can identify and evaluate these pathological biomarkers, namely neoangiogenesis, hyperemia, and hypoxia, may shed new light on research and clinical management of inflammatory arthritis. Magnetic resonance imaging (MRI) has been used to identify increased vascularity related to inflammatory arthritis and assess the hemoglobin oxygenation in arthritis with a rabbit model 6 , 7 . However, the high cost and controlled access can limit the widespread use of MRI for general clinical screening and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 The proliferative and invasive nature of arthritis synovium has frequently been compared to tumor development, both of them exhibit the apparent paradoxical features of hypoxia and angiogenesis. 59 The space of rabbit's knee joints was narrow, thus the periarticular aspect of the knee rather than the synovial microvascular response was evaluated.…”
mentioning
confidence: 99%